2007
DOI: 10.1177/1029864907011001031
|View full text |Cite
|
Sign up to set email alerts
|

Intensity changes and perceived similarity: Inter-parametric analogies

Abstract: Music theorists and psychologists have described diverse musical processes in terms of changes (increase or decrease) in "intensity". This paper examines the hypothesis that analogous intensity changes in different musical parameters can be perceived as similar, and discusses implications of such perception for music analysis. In the experiment reported, participants rated the degree to which members of pairs of musical stimuli were similar in character to a "standard" -a crescendo on a repeated tone. One memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Correspondingly, Eitan and Granot (2007) have demonstrated that changes in different musical parameters, including loudness, pitch direction, and tempo (though only when coupled with ascending pitch) can be perceived as comparable intensity changes. We assume that such intensity changes will affect tension ratings: crescendo, accelerando, and pitch rise (increases in intensity) will all be associated with higher tension ratings, while diminuendo, ritardando, and pitch fall will be associated with lower tension ratings.…”
Section: Intensification Leads To Overall Higher Tension Ratingsmentioning
confidence: 94%
See 1 more Smart Citation
“…Correspondingly, Eitan and Granot (2007) have demonstrated that changes in different musical parameters, including loudness, pitch direction, and tempo (though only when coupled with ascending pitch) can be perceived as comparable intensity changes. We assume that such intensity changes will affect tension ratings: crescendo, accelerando, and pitch rise (increases in intensity) will all be associated with higher tension ratings, while diminuendo, ritardando, and pitch fall will be associated with lower tension ratings.…”
Section: Intensification Leads To Overall Higher Tension Ratingsmentioning
confidence: 94%
“…Another relevant study employing systematic manipulation of musical parameters is Eitan and Granot (2007), examining whether changes in musical parameters, including "increase" or "decrease" in loudness, pitch, and tempo, are perceived as analogous. Parameters investigated included pitch direction (up or down) and attack rate (accelerando vs. ritardando) and all their combinations, pitch interval size (increasing vs. decreasing), and two measures of harmonic stability.…”
Section: T E N S I O N Is O N E O F T H E M O S T F U N Da M E N Ta Lmentioning
confidence: 99%
“…Both kindergarten children (Van Zee, 1976) and fourth graders (Andrews & Deihl, 1970) tended to use terms such as high/low, large/small fast/slow and loud/soft interchangeably for different musical dimensions. This "confusion" may reflect sensitivity to amodal features such as intensity, that associate states of higher (high pitch, loud volume, fast pace) and lower intensity in different musical dimensions (Eitan, 2007;Eitan & Granot, 2007).…”
Section: Developmental Issuesmentioning
confidence: 99%
“…The relationships of ascending pitch with increasing distance and speed, or of pitch descent with leftward motion, found for adults in Eitan & Granot (2006), cannot be easily derived from direct experience with sound. Rather, they may be related to an abstract scheme, mapping different parameters onto a quantitative scale (Eitan & Granot, 2007;Eitan, 2007). Even the entrenched verticality metaphor was used by children more consistently for loudness than for pitch, perhaps due to the concrete relationships of loudness with larger physical dimensions.…”
Section: Corroborating Previous Findingsmentioning
confidence: 99%
“…As Levinson or Gurney would suggest, the participants' sense of incoherence may be primarily based on the presence of local contrasts between adjacent events, rather than on global or remote relationships. Moreover, as several empirical studies have indicated, listeners' judgments of thematic similarity often rely on musical dimensions such as dynamics, pitch register, and texture, rather than on the dimensions that most music theorists view as the bases of musical unity, such as tonal relationships and pitch intervals (Eitan & Granot, 2007;Lamont & Dibben, 2001;Ziv & Eitan, 2007). Simple auditory cues, not specific to music, thus play a central role in similarity perception and categorization in music, even in those musical styles (such as the Classical style) where, according to established music theories, they are supposed to be almost irrelevant to such tasks.…”
Section: Inner Unity and Perceived Coherencementioning
confidence: 99%